Combined visual and motor disorganization in patients with schizophrenia - Giersch, Anne; Wilquin, Hélène; Capa, Rémi L.; Delevoye-Turrell, Yvonne N. (Frontiers in Psychology, 2013)
Cognitive impairments are difficult to relate to clinical symptoms in schizophrenia, partly due to insufficient knowledge on how cognitive impairments interact with one another. Here, we devised a new sequential pointing task requiring both visual organization and motor sequencing. Six circles were presented simultaneously on a touch screen around a fixation point. Participants pointed with the finger each circle one after the other, in synchrony with auditory tones. We used an alternating rhythmic 300/600 ms pattern so that participants performed pairs of taps separated by short intervals of 300 ms. Visual organization was manipulated by using line-segments that grouped the circles two by two, yielding three pairs of connected circles, and three pairs of unconnected circles that belonged to different pairs. This led to 3 experimental conditions. In the ‘congruent condition’, the pairs of taps had to be executed on circles grouped by connecters. In the ‘non congruent condition’, they were to be executed on the unconnected circles that belonged to different pairs. In a neutral condition, there were no connecters. 22 patients with schizophrenia with mild symptoms and 22 control participants performed a series of 30 taps in each condition. Tap pairs were counted as errors when the produced rhythm was inverted (expected rhythm 600/300=2; inversed rhythm<1). Error rates in patients with a high level of clinical disorganization were significantly higher in the non-congruent condition than in the two other conditions, contrary to controls and the remaining patients. The tap-tone asynchrony increased in the presence of connecters in both patient groups, but not in the controls. Patients appeared not to integrate the visual organization during the planning phase of action, leading to a large difficulty during motor execution, especially in those patients revealing difficulties in visual organization. Visual motor tapping tasks may help detect those subgroups of patients.